Identification of genes associated with intramuscular fat deposition and composition in Nellore breed - Cesar, Aline Silva Mello (2014)
The amount and composition of intramuscular fat (IMF) influence the sensory characteristics, nutritional value of beef and human health. The amount of fatty acid and its composition in beef varies by breed, nutrition, sex, age or carcass finishing level. The fat deposition and composition are determined by many genes that participate directly or indirectly in adipogenesis and lipid metabolism. The selection of animals with fat amount and composition suitable for the consumer is complex due to high cost of measurement, the moderate heritability and polygenic traits (many genes are involved with these traits). In the last decade with a great advance in bovine genomics resulted in the complete genome sequencing and the development of high-density chips of SNPs. This scientific advance jointly with technological improvement allowed the identification of genes responsible for important quantitative traits in cattle. This study aimed to identify and characterize genes associated with the deposition and composition of intramuscular fat in Nellore. A genome-wide association study (genome- wide association studies, GWAS) was performed to identify genomic regions associated with traits of interest and positional candidate genes. A total RNA sequencing (RNA-Seq) analysis was applied to transcriptome study of Longissimus dorsi muscle. Three hundred and eighty six Nellore steers were used for the evaluation of lipid content and fatty acid profile of LD, and genotyping with high-density chip SNP (SNP800 Illumina BeadChip). A subset of 14 animals, seven animals for each extremes of genomic estimated values (GEBV) were used to RNA-Seq analysis. Twenty-five genomic regions (1 MB window) were associated with the deposition and composition of intramuscular fat, which explained >= 1 % of the genetic variance. These regions were identified on chromosomes 2, 3, 6, 7, 8, 9, 10, 11, 12, 17, 26 and 27, many of these have not previously been found in other breeds and in these regions important genes were identified. Genomic regions and genes identified and presented here should be contribute to a better understanding of the genetic control of deposition and fat composition in beef cattle, and can be applied in breeding programs for animals that produce a quality and healthy beef to human consumers.